(untitled) (Development Service Industry Management, 2023)
The article emphasizes the importance of solving employment problems and overcoming the causes of unemployment. The main emphasis is placed on the category of self-employed persons and on the involvement of the leadership factor within social and labor relations. The purpose of the study is to improve the theoretical, methodological and applied principles of managing the development of leadership qualities of self-employed persons in crisis conditions. It is shown that despite the existence of publications devoted to the functioning and improvement of social and labor relations, employment, etc., as well as leadership, leadership in the segment of self-employed persons remains insufficiently studied and researched. New approaches, tools and means of developing leadership qualities and potential of self-employed persons have been developed. It is shown that in a crisis situation, namely in the conditions of war, the demand for the services of self-employed persons in Ukraine is rapidly growing, in particular in the field of design and art, programming, work with texts, audio and video, outsourcing and consulting, mobile applications, translations, programming . An algorithm of measures for the formation and realization of the leadership potential of self-employed persons has been developed. Features of such stages of the algorithm as institutionalization of activity are determined; description of general leadership characteristics in the selected type of economic activity; development and implementation of own internal methodical support for managing the development of leadership potential; planning activities for the formation of leadership potential; determination of functional and structural characteristics of leadership potential; approval of the program for the development of leadership qualities and characteristics; implementation of accumulated leadership functions. The leading leadership functions of self-employed persons include: managing one’s own professional culture, professional self-development, realizing one’s own inherent human potential, avoiding professional and other conflicts, establishing high-quality communication in one’s own business environment, especially digital relations and connections.